Heat transfer characteristics of flat and concave surfaces by circular and elliptical jet impingement. Issue 7 (10th November 2022) - Joshi, Jaykumar; Sahu, Santosh Kumar
ABSTRACT: The present paper reports the thermal behavior of flat and curved surfaces with impinging jets employing circular and elliptical nozzle for identical equivalent diameter (de ). Tests are performed with the Reynolds number varying from 11, 250–22, 500, varied range of plate to nozzle distance ( z/d = 1–6), various nozzle aspect ratios ( AR = 1–4). A comparison of thermal behavior between flat and concave surfaces ( d/D = 0.05) is discussed in this study. The maximum enhancement in the stagnation Nusselt number found to be 27.4% and 24.8% with the increase in AR = 1 to 4 for flat surface, curved surface, respectively.